2022
DOI: 10.1200/jco.2022.40.16_suppl.1037
|View full text |Cite
|
Sign up to set email alerts
|

Updated results and biomarker analyses from the phase I trial of A166 in patients with HER2-expressing locally advanced or metastatic solid tumors.

Abstract: 1037 Background: A166, an antibody-drug conjugate, with an anti-HER2 antibody site-specifically conjugated to Duo-5 (anti-microtubule agent), via a stable protease-cleavable valine citrulline linker, has proved its safety and efficacy in patients with HER2 positive breast cancer (Xichun Hu et al. ASCO 2021). Here, we report updated data and biomarker analyses from this single-arm, multi-center, open-label, phase I trial (CTR20181301). Methods: This study has two parts: dose escalation and dose expansion. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A166. A166 is a trastuzumab-based ADC linked to duostatin-5, an anti-microtubule agent, which in a phase 1/2 clinical trial demonstrated good tolerability and a promising antitumor effect in heavily pretreated breast cancer patients (NCT03602079) [ 123 , 124 , 125 ].…”
Section: Her2-targeted Therapiesmentioning
confidence: 99%
“…A166. A166 is a trastuzumab-based ADC linked to duostatin-5, an anti-microtubule agent, which in a phase 1/2 clinical trial demonstrated good tolerability and a promising antitumor effect in heavily pretreated breast cancer patients (NCT03602079) [ 123 , 124 , 125 ].…”
Section: Her2-targeted Therapiesmentioning
confidence: 99%
“…For instance, some important toxicities of the new ADCs were not commonly observed either with T-DM1 or other HER2-targeted agents, namely ocular toxicities, an important class of AEs observed with trastuzumab duocarmazine, A166, ARX788, and other agents. 62,63,68 Beyond HER2: investigational ADCs exploring other targets for the treatment of BC Although considerable research efforts have been employed in the search for new therapeutic targets in the last decades, it was only with the approval of SG for the treatment of TNBC in 2021 that an ADC targeting a non-HER2 target was incorporated into clinical practice. 28 The benefit demonstrated with this anti-Trop-2 agent proved the concepts that a new generation of ADC could effectively target proteins that are highly expressed in tumors, even if they are not part of hyperactivated oncogenic driver pathways.…”
Section: Incorporation Of Adcs Into Bc Clinical Practice Guidelinesmentioning
confidence: 99%
“…For instance, some important toxicities of the new ADCs were not commonly observed either with T-DM1 or other HER2-targeted agents, namely ocular toxicities, an important class of AEs observed with trastuzumab duocarmazine, A166, ARX788, and other agents. 62 , 63 , 68 …”
Section: Her2-targeted Adcs In Clinical Development For the Treatment...mentioning
confidence: 99%
“…[30] Yamazaki et al successfully constructed dual-payload ADCs carrying MMAE and monomethyl auristatin F (MMAF) and attributed their significant therapeutic effect against HER2 heterogeneous tumors to the bystander effect of MMAE. [31] Although several ongoing clinical trials have revealed the potential of novel permeable payloads in treating heterogeneous tumors, [32,33] the lack of comprehensive method for rational identification of bystander payloads and ADCs limited the clinical potential of this strategy.…”
Section: Introductionmentioning
confidence: 99%